Adaptive inverse control - Widrow, Bernard (Prentice Hall information and system sciences series, 1996)
This work describes a practical real-time on-line application: the control of the electron and positron beams of the Stanford Linear Accelerator. It also offers examples and simulations concerned with noise control.